2022
DOI: 10.1186/s13063-022-06137-8
|View full text |Cite
|
Sign up to set email alerts
|

The Mirasol Evaluation of Reduction in Infections Trial (MERIT): study protocol for a randomized controlled clinical trial

Abstract: Background Transfusion-transmitted infections (TTIs) are a global health challenge. One new approach to reduce TTIs is the use of pathogen reduction technology (PRT). In vitro, Mirasol PRT reduces the infectious load in whole blood (WB) by at least 99%. However, there are limited in vivo data on the safety and efficacy of Mirasol PRT. The objective of the Mirasol Evaluation of Reduction in Infections Trial (MERIT) is to investigate whether Mirasol PRT of WB can prevent seven targeted TTIs (mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…All donors are screened for serological evidence of the four major TTIs using an ARCHITECT (Abbott) platform: human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), and Treponema pallidum (syphilis). As part of the MERIT, additional blood is collected in ethylenediamine tetraacetic acid (EDTA) tubes from the diversion pouch for further testing 13 . MERIT samples were collected from October 2019 to April 2022 in Kampala, Uganda, separated into plasma and red cell pellets, and stored at −80°C until testing.…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All donors are screened for serological evidence of the four major TTIs using an ARCHITECT (Abbott) platform: human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), and Treponema pallidum (syphilis). As part of the MERIT, additional blood is collected in ethylenediamine tetraacetic acid (EDTA) tubes from the diversion pouch for further testing 13 . MERIT samples were collected from October 2019 to April 2022 in Kampala, Uganda, separated into plasma and red cell pellets, and stored at −80°C until testing.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Samples were collected as a part of the Mirasol Evaluation of Reduction in Infections Trial (MERIT), a randomized clinical trial located in Uganda investigating the effect of a riboflavin plus UV light pathogen reduction technology on the incidence of transfusion transmitted infections (TTIs). 13 The Ugandan Blood Transfusion Services (UBTS), which is responsible for all blood collections in Uganda, 14,15 collects approximately 300,000 units of blood a year. UBTS supplies fresh nonleukocyte-reduced whole blood units for MERIT and only collects blood from voluntary nonremunerated donors.…”
Section: Participants and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, prior authors have suggested the utility of PRT in various countries in Africa given the high prevalence of transfusion-transmitted infections (TTI), reliance on high-risk donors, and suboptimal testing. [15][16][17] Notably, some institutions reported collecting blood onsite from patients themselves, with many relying on rapid diagnostic tests (RDTs) for infectious disease screening, despite their inadequate sensitivity to particular infectious agents. [18][19][20][21][22][23][24] This high utilization of RDTs, which are generally accepted to not be ideal for TTI testing, [18][19][20][21][22][23][24] is likely secondary to a lack of other feasible options.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 To introduce more sensitive detection methods would increase costs dramatically and further reduce the donor pool. 25 This constellation of results indicates further studies are needed to assess barriers to implementation of PRT, 17 areas for improvement in infectious disease screening, and how blood donors are selected.…”
Section: Discussionmentioning
confidence: 99%